0195 Influences of Screen Media Use Near Bedtime on Daytime Sleepniess and Self-satisfaction among College Students: The Mediating Effect of Valid Sleep Time. (27th April 2018) - Yang, J; Yang, Q; Mai, Z; Zhou, X; Ma, N
Abstract: Introduction: Screen media use near bedtime has been shown to impact sleep quality adversely, and may lead to the compression of sleep duration. However, few studies have extracted valid sleep time from total sleep time and examined whether the exposure to screen media near bedtime is associated with daytime sleepiness and self-satisfaction. Here we sought to investigate the effects of total usage of light-emitting electronic equipment before bed (TU-LE) on sleep structure and its further effects on daily performance and self-satisfaction evaluation among Chinese college students. Methods: 3639 healthy college students (mean age ± SD: 19.6 ± 1.6) participated the survey. Data collection was conducted by paper-pen questionnairs. Associations between TU-LE, sleep indices, daytime sleepiness, and self-satisfaction were examined using hierarchical linear regression. Specifically, sleep indices included total sleep time (TST), sleep onset latency (SOL), and valid sleep time (VST), while self-satisfaction was constituted by health satisfaction, study satisfaction, and sleep satisfaction. Results: TST ranged from 6.0 to 7.9 h (mean=7.1, SD=0.9) and SOL varied from 0.1 to 0.5 h (mean=0.3, SD=0.2), while VST was the difference between TST and SOL. The regression results indicated that TU-LE could predict daytime sleepiness level positively and VST negatively, while VST could predict daytime sleepiness level positively. After controlling for VST, the relation between TU-LE and daytime sleepiness level was still statistically significant. When we further examined the factor self-satisfaction, its components were predicted by TU-LE negatively and VST positively. With VST being controlled, TU-LE could still predict those three components. Conclusion: These findings suggest that individuals reporting higher quantity of TU-LE had shorter valid sleep time, leading to worse daytime performance and self-satisfaction evaluation. Sleep education should take into consideration the cumulative effect of TU-LE. Support (If Any): National Natural Science Foundation of China 31500906 and National Basic Research Program of China (973 Program: 2015CB856400)